Fighting for Talent: Risk-shifting, Corporate Volatility, and Organizational Change - Guido Friebel; Mariassunta Giannetti (Center for Economic Studies and ifo Institute (CESifo), 2002)
In the nineties, average firm size decreased, organisations decentralized, and workers preferences shifted from large to small firms. Our model identifies the economic forces behind this trend. Small firms with little capital at risk are subject to risk-shifting. They realize more of their workers risky ideas, helping small firms to poach creative workers from better capitalized firms. This advantage increases if a) workers receive easier credit access, and b) technological progress raises the payoff from new ideas, provided that it remains very difficult to distinguish good ideas from bad ideas. As small firms take excessive risk, average enterprise profitability decreases, while bankruptcy increases. Moreover, large firms react through ineffecient organizational changes.
Keywords: 330; financial development; spin-offs; sorting; organizations; markets